PENGARUH PENGETAHUAN KEBENCANAAN TERHADAP KESIAPSIAGAAN MENGHADAPI BENCANA GEMPA PADA SISWA MADRASAH IBTIDAIYAH NEGERI 1 BOGORPENGARUH PENGETAHUAN KEBENCANAAN TERHADAP KESIAPSIAGAAN MENGHADAPI BENCANA GEMPA PADA SISWA MADRASAH IBTIDAIYAH NEGERI 1 BOGOR - Mahfudin, Muhamad; Hasanah, Tita; Huda, Samsul (Prodi PGMI IAI Sahid, 2025)
Indonesia is a country prone to disasters, one of which is earthquakes. This study aims to determine the effect of disaster knowledge on preparedness for earthquake disasters. This research approach uses quantitative. The location of the study was Madrasah Ibtidaiyah Negeri 1, Bogor Regency. The sampling technique was total sampling consisting of 51 grade 5 students. Data analysis conducted by researchers using product moment correlation test, significance test and determinant test. The results of the product moment correlation test indicate that there is an influence between disaster knowledge on preparedness for earthquake disasters. The results of the t-test indicate that there is a significant influence between disaster knowledge on preparedness for earthquake disasters. The results of the determination coefficient test obtained a value of 94%. Thus, it can be concluded that preparedness for earthquake disasters is influenced by disaster knowledge by 94% while the rest is determined by other factors. Suggestions are addressed to the principal and teachers, to make better efforts in instilling disaster knowledge in students.